1990
DOI: 10.1164/ajrccm/141.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Processing of Sequential Bronchoalveolar Lavage to Separate Bronchial and Alveolar Samples

Abstract: Bronchoalveolar lavage has been widely used to sample the lower respiratory tract. Most of the material recovered with this technique represents alveolar contents. A number of modifications have been suggested in order to obtain samples relatively enriched for bronchial material. In order to be able to use a standard technique for bronchoalveolar lavage to sample both airways and "routine" alveolar material, a simple modification of the technique as described by Reynolds and Newball was used: five sequential 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(106 citation statements)
references
References 9 publications
9
96
1
Order By: Relevance
“…In these control groups, the percentage of neutrophils was higher in the bronchial lavage fluid than in the bronchoalveolar lavage fluid. This result also is in accordance with other report (16). The presence of bronchial epithelial cells in bronchial lavage fluids of the control groups was due to recovery of infused saline at a higher negative pressure.…”
Section: Methodssupporting
confidence: 93%
“…In these control groups, the percentage of neutrophils was higher in the bronchial lavage fluid than in the bronchoalveolar lavage fluid. This result also is in accordance with other report (16). The presence of bronchial epithelial cells in bronchial lavage fluids of the control groups was due to recovery of infused saline at a higher negative pressure.…”
Section: Methodssupporting
confidence: 93%
“…However, it is clear that smaller volumes are associated with a larger bronchial component. In comparing the yield from the first 20 mL of introduced fluid to the remaining fluid, RENNARD et al [29] found a higher percentage of epithelial cells and a lower percentage of alveolar macrophages. Further studies by that group found higher levels of lactoferrin, a protein made by bronchial cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…The need for higher numbers of cells may limit the use of microscope slide smears in situations where the yield of cells may be low, e.g. the "bronchial" sample resulting from small lavage volumes [17], or when large numbers of BALF cells are needed for other purposes, e.g. in vitro culture of macrophages.…”
Section: Discussionmentioning
confidence: 99%